Problematika Penerapan Kurikulum Merdeka Dalam Mata Pelajaran Pendidikan Agama Islam - Mustofa, Ali; Oktavia, Viona; Himami, Ahmad Shofiyul (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2023)
This study aims to analyze the implementation of the Merdeka Curriculum in Islamic Religious Education (PAI) learning at SMP Negeri 2 Diwek and its problems. A qualitative approach was used with data collection techniques through in-depth interviews and observations. The results showed that the Merdeka Curriculum had been implemented for one year through student-centered learning, the development of the Pancasila Student Profile, and the provision of flexibility in choosing teaching materials. The obstacles found included the diversity of student characteristics, low motivation, limited facilities and infrastructure, difficulties in assessment, teacher workload, and limited learning time. Recommended solutions include mapping student characteristics, differentiated instruction, increased motivation, development of instructional media, assessment training, coordination to reduce teacher burden, optimization of time allocation, integration of PAI values, and student guidance services. Collaborative implementation of these solutions can improve the quality of the Merdeka Curriculum implementation in PAI learning to realize national education goals.